Islamic Constitutionalism Before Sovereignty: Two Defenses of the Tunisian Constitution of 1861 (American Journal of Islam and Society, 2020)
This article focuses on the Tunisian constitutional moment of 1857-1861. Its goal is to explore an important moment in Islamic modernity for the purposes of drawing a contrast with twentieth-century, post-caliphal Islamist thought. The primary themes visible in nineteenth-century Islamic constitutional thought are a “descending” conception of sovereign constituent power with a strong emphasis on the pre-political existence of a divine law that is both binding and guiding but not necessarily the exclusive source of lawmaking. The debates of the 1860s and Ottoman constitutionalism more generally do not lead directly to a non-sovereigntist political vision. But they are representative of a pre-colonial (and thus, to a certain extent, pre-apologetic) Islamic thought that centralizes the public interest, the varieties of political judgment, and the compatibility of distinct kinds of expertise with a desacralized centralized authority. This period may hold relevance for our present moment when twentieth-century ideals of both divine and popular sovereignty seem to no longer dominate Islamic (and Islamist) approaches to political life.